Diethyl trans-2,5-bis(4-methoxybenzylsulfanyl)-1,4-dimethyl-3,6-dioxopiperazine-2,5-carboxylate - Nathan W. Polaske; Gary S. Nichol; Bogdan Olenyuk (Acta Crystallographica Section E, 2009)
The title compound, C28H34N2O8S2, was synthesized as part of a project to develop synthetic routes to analogues of sporidesmins, a class of secondary metabolite produced by the filamentous fungi Chaetomium and Pithomyces sp. The complete molecule is generated by crystallographic inversion symmetry: the methoxy group is essentially coplanar with the benzene ring to which it is bonded, a mean plane fitted through the non-H atoms of the aromatic ring and the methoxy group having an r.m.s. deviation of 0.0140 Å. Similarly, the ester group is also essentially planar (r.m.s. deviation of a plane fitted through all non-H atoms is 0.0101 Å). There is only one independent C—H...O interaction, which links together adjacent molecules into a two-dimensional sheet in the bc plane.